The diamond caper - Mayle, Peter (Mayle, Peter. Sam Levitt mysteries., 2015)
When a Riviera socialite's diamonds are stolen--the latest in a string of seemingly unconnected but ever-more-audacious jewelry heists across France--Elena flies in to investigate the insurance claim. It's a trip she's more than happy to make, as it gives her a chance to meet up with old friends in Marseille--and, particularly, with Sam. Once reunited, Sam isn't entirely distracted by domestic matters. In the pattern of these "perfect crimes" he's beginning to see a master at work, and he's quickly determined to connect and solve the cases. But as he and Elena dig deeper, they begin to realize just how much is connected and how dangerous it may be to pursue the whole truth.